IN VITRO PROTEIN DIGESTIBILITY OF MILLET MEAL PREPARATIONS - V. DURGA RANI, JANE BRIDGET KANDEH, K. UMA DEVI , K. UMA MAHESWARI, T. SARAH KAMALA and (The Journal of Research, PJTSAU, 2019)
Six different millet products have been developed and standardized to serve as most common lunch dishes namely millet rice, kichidi and roti using traditional local recipe adopted for cereals. The overall mean in vitro protein digestibility (IVPD) of millet kichidi from 6 millets was 66.93 Â± 3.78%, and it was significantly high (P<0.01), compared to the mean IVPD of millet roti, millet rice and raw millet in the decreasing order. Mean IVPD of millet roti, millet rice, and raw millet from the 6 millets showed no significant difference indicating that, dry roasting as in roti and wet cooking as in millet rice did not have much effect on digestibility of millets. Boiling as rice improved IVPD of finger millet and sorghum, but not in other millets. Dry roasting in roti improved IVPD in dehulled millets. Addition of legumes in kichidi improved protein quantity and protein digestibility in vitro. The difference of IVPD in millets varied from 3 to 10%.